চয়নিকা - Bakul Chandra Chowdhury (My University, 1996)
This book is an Advanced Course consisting of 22 Units on learning. It aims at giving the learners the taste of the representative samples of literature in Bengali.
Advanced Course Reader in Bengali (CHAYANIKA)
Keywords: Bengali